2018
DOI: 10.5539/jas.v10n12p377
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Mathematical Models of the Drying Kinetics and Physicochemical Quality of the Chili Pepper

Abstract: The present work had as objective to determine the kinetics of drying of the chili pepper, to adjust different mathematical models to the experimental values as a function of the water content and to characterize the same in it’s in natura form and after the drying in the temperatures of 60, 70 and 80 °C. The samples were weighted periodically until reaching the equilibrium. The mathematical models of Wang and Singh, Henderson and Pabis, Newton, Page and Thompson were adjusted to the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Several mathematical models have been used to describe the drying process of agricultural products and to determine process information, which can be used in future equipment designs. These analytical solutions are used to describe the thin‐layer drying of various agricultural products, besides determining the effective mass flow diffusivity and convective mass transfer coefficient (Da Silva et al, 2010; Meneghetti et al, 2012; Menezes, Ströher, Pereira, & Barros, 2013; Silva et al, 2018b). In general, a diffusion model is important because it allows simulating the distribution of moisture over time.…”
Section: Resultsmentioning
confidence: 99%
“…Several mathematical models have been used to describe the drying process of agricultural products and to determine process information, which can be used in future equipment designs. These analytical solutions are used to describe the thin‐layer drying of various agricultural products, besides determining the effective mass flow diffusivity and convective mass transfer coefficient (Da Silva et al, 2010; Meneghetti et al, 2012; Menezes, Ströher, Pereira, & Barros, 2013; Silva et al, 2018b). In general, a diffusion model is important because it allows simulating the distribution of moisture over time.…”
Section: Resultsmentioning
confidence: 99%
“…Derlan et al (2013), when evaluating the drying process of cambuci pepper at 40, 50 and 60°C, determined that the Midili model was the best fit for the experimental data. Silva et al (2018b) found that the Handerson and Pabis model best described the drying process of peppers at temperatures of 60 to 80°C. Figure 1 shows the Page model as the one that best described the drying kinetics of yellow pepper to the drying air temperatures applied.…”
Section: Resultsmentioning
confidence: 99%
“…The Page model was considered as the lowest values for the same function with a variation of 0.3399 to 0.5183 × 10 -2 between the applied temperatures, being the model chosen to represent the drying process. The Peleg model also presented high R 2 and low χ2, according to Silva et al (2018b), it can be interpreted as an equation resulting from the law of second-order drying rate, which allows to give a physical meaning to the parameters obtained by adjusting curves (Pan et al, 2011;Tao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%